2020
DOI: 10.1061/(asce)gm.1943-5622.0001562
|View full text |Cite
|
Sign up to set email alerts
|

Development and Verification of a New Simplified Method for Calculating Settlement of a Thick Soil Layer with Nonlinear Compressibility and Creep

Abstract: The variable compressibility is necessary to be considered in settlement calculation of soft soil stratums, especially for thick soil layers. In this study, to calculate the consolidation settlement of a thick soil layer with creep, a new simplified method is presented using Zhu and Yin method (2012) to consider the nonlinear compressibility. The creep settlement during the consolidation stage is calculated, examined, and discussed for the thick soil layer. In the new simplified method, α is an important param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
5
0
2
Order By: Relevance
“…Según, (Feng & Yin, 2019) la consolidación de los suelos arcillosos se ve directamente afectada por el suelo compresible, en la teoría de Terzaghi la relación esfuerzo a tensión de los suelos es lineal, lo que significa que la compresibilidad del suelo es una constante, sin embargo, la comprensibilidad de los suelos blandos es estrechamente relacionado con las tensiones efectivas iniciales y finales a lo largo de la profundidad. (Olek, 2019) la teoría de consolidación 1-D de Terzhahi se usa comúnmente para predicción de asentamiento de taludes en suelos blandos de grano fino, sin embargo, esta teoría no siempre es efectiva debido a las simplificaciones asumidas en el comportamiento del suelo bajo carga, Considerando el asentamiento por consolidación de un suelo arcilloso que calcula normalmente consolidada basado en la condición 1D dada en la ecuación (1).…”
Section: La Teoría De Terzaghi -Consolidación Unidimensionalunclassified
See 1 more Smart Citation
“…Según, (Feng & Yin, 2019) la consolidación de los suelos arcillosos se ve directamente afectada por el suelo compresible, en la teoría de Terzaghi la relación esfuerzo a tensión de los suelos es lineal, lo que significa que la compresibilidad del suelo es una constante, sin embargo, la comprensibilidad de los suelos blandos es estrechamente relacionado con las tensiones efectivas iniciales y finales a lo largo de la profundidad. (Olek, 2019) la teoría de consolidación 1-D de Terzhahi se usa comúnmente para predicción de asentamiento de taludes en suelos blandos de grano fino, sin embargo, esta teoría no siempre es efectiva debido a las simplificaciones asumidas en el comportamiento del suelo bajo carga, Considerando el asentamiento por consolidación de un suelo arcilloso que calcula normalmente consolidada basado en la condición 1D dada en la ecuación (1).…”
Section: La Teoría De Terzaghi -Consolidación Unidimensionalunclassified
“…De otro lado, (Yongqiang et al, 2015) mencionan que las características de los cimientos de suelos blandos mejorados se analizan desde una perspectiva numérica; se hacen modelos para evaluar sus efectos, bajo la especificación de la teoría de consolidación unidimensional. También, (Feng & Yin, 2019) proponen un método simplificado para calcular el asentamiento de una capa gruesa de suelo con fluencia, esto evita tediosos métodos numéricos para obtener el asentamiento total, se basa en una solución matemática para el análisis de consolidación de una capa de suelo para considerar la compresibilidad no lineal, concluyendo que fue consistente con los datos medidos. Posteriormente, (Qi & Simms, 2019) proponen nuevos enfoques para determinar de manera robusta las funciones de comprensibilidad y permeabilidad, para el gran esfuerzo de consolidación, utilizando mediciones limitadas de pruebas unidimensionales, como experimentos de columnas o centrífuga.…”
unclassified
“…where σ is the total stress, γ w is the unit weight of water, t is the time, and z is the depth. Using the Galerkin weighted residual method [30], Equation ( 9) can be converted to Equation (10):…”
Section: Finite Element Equationsmentioning
confidence: 99%
“…To improve the calculation accuracy, many modifications of the assumptions have been proposed. Past studies mainly investigated the variations of material parameters, such as the permeability and the compressibility [3][4][5][6][7][8][9][10], and many advances related to varying loading, which better reflect real constructions, were obtained [11][12][13][14][15]. As a simplification of inhomogeneity along depth, multilayered soil was studied [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Dumais and Konrad [7] established a one-dimensional model for the consolidation of thawed soil by using the relationship among effective stress, void ratio, and permeability coefficient. Yin and Feng [8,9] stated that the variable compressibility must be considered in settlement calculation of soft soil stratum and proposed a new simplified method to calculate the settlement of a thick soil layer by considering the nonlinear compressibility. Besides, a onedimensional nonlinear consolidation theory considering the thermal effect was established, which showed that the pore water dissipation rate or consolidation rate considering the secondary consolidation and temperature was higher than that when only considering secondary consolidation [10].…”
Section: Introductionmentioning
confidence: 99%